Identification of a β1/β2‐Specific Sulfonamide Proteasome Ligand by Crystallographic Screening. Issue 38 (4th August 2015) - Beck, Philipp; Reboud‐Ravaux, Michèle; Groll, Michael
Abstract The proteasome represents a validated drug target for the treatment of cancer, however, new types of inhibitors are required to tackle the development of resistant tumors. Current fluorescence‐based screening methods suffer from low sensitivity and are limited to the detection of ligands with conventional binding profiles. In response to these drawbacks, a crystallographic screening procedure for the discovery of agents with a novel mode of action was utilized. The optimized workflow was applied to the screening of a focused set of compounds, resulting in the discovery of a β1/β2‐specific sulfonamide derivative that noncovalently binds between subunits β1 and β2. The binding pocket displays significant differences in size and polarity between the immuno‐ and constitutive proteasome. The identified ligand thus provides valuable insights for the future structure‐based design of subtype‐specific proteasome inhibitors.